The role of animal models in unravelling therapeutic targets in coeliac disease. Issue 3 (June 2015) - Costes, Léa M.M.; Meresse, Bertrand; Cerf-Bensussan, Nadine; Samsom, Janneke N.
Abstract Coeliac disease is a complex small intestinal enteropathy that develops consequently to a breach of tolerance to gliadin, a storage protein abundantly found in cereals such as wheat, rye and barley. The understanding of the mechanisms underlying the development of coeliac disease in HLA-DQ2 and HLA-DQ8 genetically susceptible individuals has greatly improved during the last decades but so far did not allow to develop curative therapeutics, leaving a long-life gluten free diet as the only treatment option for the patients. In order to bring new therapeutic targets to light and to test the safety and efficacy of putative drugs, animal models recapitulating features of the disease are needed. Here, we will review the existing animal models and the clinical features of coeliac disease they reflect and discuss their relevance for modelling immune pathways that may lead to potential therapeutic approaches.